Does Same-Day Postoperative Increased Intraocular Pressure Affect Endothelial Cell Density After Descemet Membrane Endothelial Keratoplasty?. Issue 12 (December 2018) - Fajgenbaum, Mark A. P.; Hollick, Emma J.
Abstract : Purpose: High intraocular pressure (IOP) is common in association with intracameral air and gas tamponade after Descemet membrane endothelial keratoplasty (DMEK); yet its influence on endothelial cell survival is unknown. Our aim was to determine the effect of high IOP measured 2 hours after DMEK on 1-month endothelial cell density (ECD). The influence of other potentially relevant factors was also investigated. Methods: Retrospective, consecutive series. Inclusions: low-to-moderate risk DMEK surgery alone or combined with phacoemulsification. Exclusions: previous penetrating keratoplasty or glaucoma surgery; grafts with any of the following in the first month: rebubble, rejection, or graft failure. Results: Sixty-two grafts met inclusion with 60 having IOP recorded at 2 hours. Thirty-eight percent (23/60) had IOP >30 mm Hg and 22% (13/60) had IOP >40 mm Hg at 2 hours. All grafts with IOP >30 mm Hg had air released and immediate normalization of pressure. One-month ECD (mean ± standard error of mean) was 1872 ± 58 cells/mm 2, representing cell loss of 29.8 ± 2.0%. Two-hour IOP was highly insignificant against 1-month ECD when tested as a continuous variable ( P = 0.78). Lower 1-month ECD was statistically correlated with lower donor count ( P = 0.002) and combined DMEK-phaco surgery ( P = 0.01) on univariate and multivariate analysis. Insignificant factors ( P > 0.05) against 1-month ECD included patient age, sex and race, surgical indication (Fuchs endothelial dystrophy vs. non-Fuchs endothelial dystrophy), and donor age. Conclusions: Increased IOP at 2 hours is common after DMEK, but does not seem to influence early endothelial cell survival. One-month ECD was influenced by donor counts and combined cataract surgery.